2014
DOI: 10.1039/c4mb00001c
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes are juxtaposed to strategic sites on mitochondria

Abstract: Peroxisomes are ubiquitous and dynamic organelles that house many important pathways of cellular metabolism. In recent years it has been demonstrated that mitochondria are tightly connected with peroxisomes and are defective in several peroxisomal diseases. Indeed, these two organelles share metabolic routes as well as resident proteins and, at least in mammals, are connected via a vesicular transport pathway. However the exact extent of cross-talk between peroxisomes and mitochondria remains unclear. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 33 publications
7
96
0
Order By: Relevance
“…Rather, genes controlling mitochondrial function or localization were dramatically enriched. Among the top 130 mutants with enlarged peroxisomes, 80 were mitochondrial proteins (five-fold enrichment, P-value=2×10 −31 ) (Eden et al, 2009), confirming a tight connection between peroxisomes and mitochondria (Cohen et al, 2014;Mohanty and McBride, 2013;Schrader et al, 2013;Thoms et al, 2009). Indeed it is known that when mitochondrial metabolism is compromised, cells can compensate by upregulating peroxisome metabolism and size (Eisenberg-Bord and Schuldiner, 2016).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Rather, genes controlling mitochondrial function or localization were dramatically enriched. Among the top 130 mutants with enlarged peroxisomes, 80 were mitochondrial proteins (five-fold enrichment, P-value=2×10 −31 ) (Eden et al, 2009), confirming a tight connection between peroxisomes and mitochondria (Cohen et al, 2014;Mohanty and McBride, 2013;Schrader et al, 2013;Thoms et al, 2009). Indeed it is known that when mitochondrial metabolism is compromised, cells can compensate by upregulating peroxisome metabolism and size (Eisenberg-Bord and Schuldiner, 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Following a similar approach, a genome-wide screen for alterations in the expression of a GFP-labeled peroxisomal matrix protein led to the identification of 169 genes required for all the processes that lead to faithful biogenesis and propagation of peroxisomes (Saleem et al, 2010). Other systematic approaches including high-throughput experiments with quantitative analysis and modeling have been used to complete the peroxisomal proteome and to improve the understanding of peroxisome metabolism and biogenesis (Cohen et al, 2014;Wolinski et al, 2009). More recently, systematic high-content screens and bioinformatics analyses led to the identification of a new peroxisomal targeting protein, Pex9, and two new peroxisome matrix proteins, Pxp1 and Pxp2 (Effelsberg et al, 2016;Nötzel et al, 2016;Yifrach et al, 2016;Yofe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, mitochondria and peroxisomes form a contact site at the junction where mitochondria are also in contact with the ER [102]. Cells lacking subunits of the ERMES complex, the tethering complex between the ER and mitochondria, show aberrant peroxisome structure and size.…”
Section: Machinery and Functionmentioning
confidence: 99%
“…Interestingly, the authors reported that MAVS were enriched at junctions between all three organelles, where they could potentially integrate activating and repressing signals transmitted by the individual organelles. Another example for a triple contact between those three organelles was reported from S. cerevisiae [28]. Peroxisomes were additionally shown to significantly juxtapose with specialized mitochondrial regions enriched in the pyruvate dehydrogenase complex.…”
mentioning
confidence: 89%